Research on the Impact of ESG Disclosure on Green Bond Issuance in New Energy from the Perspective of Carbon peak - Han, Jinying; Zhang, Hongru (International Journal of Natural Resources and Environmental Studies, 2024)
With the goal of carbon peaking, low-carbon green development has become the main theme of economic development. In this context, while pursuing economic benefits, it is also necessary to take into account environmental benefits. Industrial development policies and matching funding strategies related to low-carbon green are called for, and sustainable economic strategies will make the industry move forward steadily. On the basis of foreign scholars' research on green bonds and industrial ESG, this project is based on the new energy industry, organizing and researching the information disclosed by its ESG, exploring in depth the influence of this information on the issuance of green bonds by the new energy industry, and exploring whether there is any positivity in this influence. The ESG information disclosed by the new energy industry can, on the one hand, help investors better understand ESG governance and the green bond market in the new energy industry, and guide them to make rational investments; on the other hand, it can help the government better formulate policies to improve the perfection of the green bond-related standards, including the evaluation system and certification system, as well as the quality of the industry's information disclosure.